Investigation of the Compressive Strengths of Coconut Shells as Partial Alternative of Coarse Aggregates in Concrete Mix - Manaloto, John Arvin R. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 9, 2023)
As the infrastructure development continues to thrive in the Philippines, the demand for concrete in the construction industry also grows. Aggregates, being one of the major components of concrete, plays a vital role in construction. The method of extracting these aggregates entails numerous environmental issues such as land degradation, water pollution, and air and dust pollution. The presence of these non-eco-friendly ways of acquiring raw materials of concrete calls for a need to explore and to find suitable material to substitute the natural stone. Alternative materials show increasing potential in concrete mix design strategies and provide new opportunities for a number of design conditions. This paper introduces the usage of agricultural wastes namely the coconut shell as a substitute to coarse aggregates. Context of concrete mix and how standard design measures are enacted. The research incorporated the crushed coconut shell into the concrete mixture as an aggregate. The physical properties of coconut shells as well as the components of concrete were presented. The compressive strength, slump test, concrete density, and air content were also presented. The slump test and compressive strength test were conducted in accordance with ASTM C143 and ASTM C39 respectively. Results show that workability of concrete is slightly affected at increasing replacement of coconut shells. Integration of coconut shells caused a 24% concrete strength reduction for every 20% coconut shell replacement at 28 days strength.